Jan Opsomer, Geert Roskam & Frances B. Titchener (eds.), A Versatile Gentleman. Consistency in Plutarch’s Writing - Leão, Delfim (2016)
Plutarch’s works — and especially the Life of Solon — are a major source for recovering of Solon’s laws. However, the biographer does not limit himself to be a simple transmitter of Solon’s legal activity: on the contrary, he comments as well on the consistency and importance of the material he is providing (sometimes for the first time and as the sole existing testimony). This paper intends to analyse the reliability of Plutarch as a legal source, taking as direct reference the laws of Solon recorded by him and considering especially those moments when he praises a regulation or on the contrary voices criticism, in order to perceive if that approach is consistent with the general scrutiny he applies to Solon’s legal activity.